Characterization of the Pharmacokinetics of Phosphatidylethanol 16:0/18:1 and 16:0/18:2 in Human Whole Blood After Alcohol Consumption in a Clinical Laboratory Study. (30th April 2016) - Javors, Martin A.; Hill‐Kapturczak, Nathalie; Roache, John D.; Karns‐Wright, Tara E.; Dougherty, Donald M.
Abstract : Background: The purpose of this study was to characterize the pharmacokinetics of 2 homologues of phosphatidylethanol (PEth) and their combined total in uncoagulated, whole blood samples taken from participants in a human clinical laboratory study after consumption of low doses of ethanol (EtOH). Methods: As part of a larger study, 14 male and 13 female participants received either 0.25 or 0.50 g/kg oral doses of EtOH during a 15‐minute period. Blood samples were collected before and throughout 6 hours after each EtOH dose on the day of consumption and then every 3 days during the next 14 days. PEth 16:0/18:1 and PEth 16:0/18:2 levels were quantified in blood samples by HPLC/MS/MS and reported separately or as their combined total (combined PEth). Breath alcohol concentrations (BrACs) were measured concurrently with each blood collection. Transdermal alcohol concentrations were measured every 30 minutes during the entire 22‐day study to confirm the absence of drinking during a 7‐day period before and the 14‐day period after EtOH consumption. Results: (i) Single doses of 0.25 and 0.50 g EtOH/kg produced proportional increases in BrAC and combined PEth levels of all participants; (ii) the areas under the curve (AUCs) for each participant's BrAC levels during the 6‐hour period after EtOH administration were correlated with AUCs of cPEth (calculated as the AUC of the increase above baseline for combined PEth); (iii) the mean half‐life of combined PEth, determined during the 14‐day period after EtOH consumption, was 4.6 ± 3.5 (SD) days (range: 1.0 to 13.1 days). Conclusions: Combined PEth is a sensitive biomarker for the identification of relatively low levels of EtOH consumption. The measurement of these 2 homologues may provide additional sensitivity to identify low levels of drinking. Abstract : The purpose of this study was to characterize the pharmacokinetics of PEth 16:0/18:1 and 16:0/18:2 in blood of 27 participants in a human laboratory study. Blood samples were collected immediately after consumption of low (0.25 and 0.50 g/kg) doses of ethanol and then every 3 days for 2 weeks during abstinence. Our results indicate that ethanol produced increased PEth levels in all participants and PEth levels correlated with absorption of ethanol. Also, the measurement of these 2 PEth homologues may provide additional information to estimate the time from last, previous drinking.